Pertanggungjawaban Pidana dengan Menggunakan Bukti Tidak Langsung (circumstantial evidence) - Bagas, Alkautsar; Mulyati, Nani; Danil, Elwi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
The use of circumstantial evidence in Indonesia's criminal justice system has sparked significant legal debate, particularly in complex cases like the Jessica Kumala Wongso trial. This research examines the application of Indirect evidence in criminal proceedings, focusing on its implications for proving criminal liability and ensuring justice. The study analyzes the Jakarta Central District Court's Decision No. 777/PID.B/2016/PN.JKT.PST, which heavily relied on circumstantial evidence to convict the defendant of premeditated murder. The research aims to evaluate the legal standing of circumstantial evidence in Indonesian criminal law, assess its impact on the principles of due process and presumption of innocence, and explore the challenges in balancing effective law enforcement with the protection of defendants' rights. Using a normative juridical approach with analytical descriptive characteristics, this study employs case study, statutory, and conceptual approaches to examine relevant laws, court decisions, and legal doctrines. The methodology involves comprehensive analysis of secondary data sources, including legislation, books, journals, and other pertinent literature. The findings highlight the need for clearer guidelines and stricter standards in the use of circumstantial evidence, emphasizing the importance of maintaining the integrity of the justice system while adapting to the complexities of modern criminal cases. This research contributes to the ongoing discourse on reforming Indonesia's criminal evidence system to better address challenges in contemporary legal practice.